Implementation of PSAK 72 in Revenue Recognition of Star Hotels in Post-Pandemic Bali - Kadek Dian Jatiwardani; Putu Esa Naranata Dewi; Ni Wayan Risna Swardani; Nyoman Angga Pradipa; Mertyani Sari Dewi (Faculty of Economics dan Business, Atma Jaya Makassar University, 2026)
This study aims to analyze the implementation of Indonesian Financial Accounting Standard (PSAK) Number 72 on Revenue from Contracts with Customers in five-star hotels in the Nusa Dua area of Bali, within the context of the post-COVID-19 tourism industry recovery. Employing a descriptive qualitative method with a multiple case study approach, data were collected through in-depth interviews with income auditors, chief accountants, and financial controllers at three five-star hotels, supported by an analysis of financial statement documents for the 2022–2023 period. Data were analyzed using the interactive model of Miles, Huberman, and Saldana (2014), comprising data condensation, data display through cross-case comparison matrices, and conclusion drawing, with triangulation to ensure validity. The findings indicate that all three hotels have formally adopted the five-step revenue recognition model of PSAK 72; however, inconsistencies were identified in the recognition of bundled room packages that include services such as breakfast, spa, and airport transfers. Furthermore, the handling of advance payments and no-show revenue has not been fully aligned with the performance obligation principles stipulated in the standard. The significant recovery in hotel performance—with occupancy rates reaching 72% and RevPAR surpassing pre-pandemic benchmarks by 37% in 2023—has driven increased complexity in revenue transactions, demanding stricter application of accounting standards. This study recommends adjustments to internal accounting policies and improvements in human resource competency in the field of tourism accounting.